2011
DOI: 10.1111/j.1365-3164.2011.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of histamine H4 receptor mRNA in the skin and other tissues of normal dogs

Abstract: The histamine 4 (H(4)) receptor was first cloned and characterized in 2000 using the human H(3) receptor DNA sequence. The H(4) receptor has been shown to participate in various aspects of inflammation, such as chemotaxis, upregulation of adhesion molecule expression and modulation of cytokine secretion. The primary goal of this study was to determine whether H(4) receptor mRNA is expressed in normal canine skin by performing an RT-PCR. An additional goal was to determine the expression of this receptor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…A very low level of H 4 receptor mRNA has been reported in the kidney of dog, monkey, rat, mouse, guinea pig and pig [14][15][16][17][18]. Despite the demonstration of an increasing histamine release in diabetic kidney, there is no evidence for the involvement of H 4 receptor expression in the diabetes-related kidney disease.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A very low level of H 4 receptor mRNA has been reported in the kidney of dog, monkey, rat, mouse, guinea pig and pig [14][15][16][17][18]. Despite the demonstration of an increasing histamine release in diabetic kidney, there is no evidence for the involvement of H 4 receptor expression in the diabetes-related kidney disease.…”
mentioning
confidence: 89%
“…Interestingly, although expression differences were observed among species [14,15,17,18,34], the similar tissue distribution in different mammals indicates conserved and comparable physiological roles of the H 4 receptor across species. Therefore, we could speculate similar roles in humans.…”
Section: Renal H 4 Receptor Expression In Diabetic Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a possible role for H 4 R has been suggested by our research group [14]. While a very low mRNA level of the latest discovered histamine receptor has been reported in the kidney of dog, monkey, rat, mouse, guinea pig and pig [15][16][17][18][19][20], in 2013 we demonstrated the presence of H 4 R in resident renal cells of the loop of Henlé!and its profound upregulation in the kidney of diabetic rats [14]. Notably, these data provide the first basis to hypothesize a possible involvement of H 4 R in the onset/progression of diabetes-associated renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, H3R has been demonstrated to be functionally absent from the canine colon, and this suggests H3R to be of minor importance for gastrointestinal function in many animals species including dogs (Rangachari and Prior, 1994). In recent studies, expression of H4R mRNA was demonstrated in various canine tissues including those of the small intestine and colon (Jiang et al, 2008;Eisenschenk et al, 2011). The expression and distribution of H1R, H2R and H4R in canine tissues at protein level, however, are unknown.…”
Section: Introductionmentioning
confidence: 95%